Rapid and Sensitive Method for Extraction of Plicosepalus acacia with Determination of Its Main Polyphenolic Compounds Using Validated HPLC - Mashail N. AlZain; Rashed N. Herqash; Abdulaziz N. Almoqbil; Omer Mohammed Almarfadi; Mansour N. Ibrahim; Riaz Ullah; Omar M. Noman (Journal of Analytical Methods in Chemistry)
Matrix solid phase dispersion (MSPD) trailed by HPLC is a quick and fruitful technique utilized for fortitude of flavonoids such as Catechin, Kaempferol, Quercetin, and Rutin existing in P. acacia. The trial parameters that influenced the extraction potential (comprising the mass ratio of sample to the dispersant, nature of dispersant, and the nature of elution solvent and its volume) were examined and optimized. These MSPD optimized parameters regulated are as follows: 8 mL of methanol was utilized as elution solvent, silica gel/sample mass ration was selected to be 2 : 1, and dispersing sorbent was silica gel. The technique retrievals were regulated to be “from 96.87 to 100.54%” and the RSDs from 1.24 to 4.45%. The product of extract obtained by MSPD method was larger than that of other methods, i.e., sonication extraction or traditional reflux with lessened necessities on time, sample, and solvent.